2015
DOI: 10.1111/mcn.12216
|View full text |Cite
|
Sign up to set email alerts
|

Lower levels of human milk adiponectin predict offspring weight for age: a study in a lean population of Filipinos

Abstract: Prior studies have reported a significant, inverse association between adiponectin in human milk and offspring growth velocity. Less is known about this association in populations characterised by a loss of weight for age z-scores (WAZs) in early life. We investigated the association between maternal body composition and milk adiponectin in a sample of Filipino mothers. We then tested for an association between milk adiponectin and size for age in their infants. A total of 117 Filipino mothers nursing infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 40 publications
3
28
0
1
Order By: Relevance
“…The temporary drop in protein concentration was consistent with differences described by Nommsen et al [42]. Whereas some studies have reported a decrease in concentrations of leptin [75] and adiponectin [30,33,36,66] (measured predominantly in skim HM), others found the opposite trend for adiponectin [11,35], no change [76] or significant fluctuations [11,21] for leptin. More research is required to clarify these relationships.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The temporary drop in protein concentration was consistent with differences described by Nommsen et al [42]. Whereas some studies have reported a decrease in concentrations of leptin [75] and adiponectin [30,33,36,66] (measured predominantly in skim HM), others found the opposite trend for adiponectin [11,35], no change [76] or significant fluctuations [11,21] for leptin. More research is required to clarify these relationships.…”
Section: Discussionsupporting
confidence: 89%
“…We have now expanded the absence of a relationship to maternal %FM and whole HM adiponectin. Thus, it is unlikely that maternal adiposity plays a major role in influencing HM adiponectin levels and it suggests the majority of HM adiponectin may be synthesized and controlled by the mammary gland [66] highlighting the importance of this HM hormone for the infant. Indeed, it appears that HM adiponectin levels regulate infant growth with higher levels of HM adiponectin being associated with lower weight for age (WAZ) and weight for length (WLZ) z -scores at 6 months of age [34] and higher WAZ and WLZ scores over the first 2 years of life [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We leveraged existing metadata of milk nutrient composition, energetic density, and hormone concentration from previous research (Anderson et al, ; Garcia et al, ; Hinde et al, ; Power et al, ; Quinn et al, ). We previously assayed a subset of samples using standard nutrient composition methods to calculate % crude protein, % total sugar, and % crude fat (Garcia et al, ; Hinde et al, ; Power et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Stężenie tego hormonu w mleku kobiecym zależy od czasu trwania laktacji, otyłości matki i rasy. Ściśle koreluje z wartością w surowicy noworodka i jego masą ciała (mc), a karmienie naturalne jest uważane za jeden z istotnych czynników chroniących dziecko przed otyłością [13][14][15][16]. Stężenie adiponektyny jest wyższe u matek rodzą-cych przedwcześnie niż o czasie [17].…”
Section: Wstępunclassified